2021
DOI: 10.3390/ijerph18031090
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Unreported COVID-19 Cases with a Time-Varying SIR Regression Model

Abstract: Background: Potential unreported infection might impair and mislead policymaking for COVID-19, and the contemporary spread of COVID-19 varies in different counties of the United States. It is necessary to estimate the cases that might be underestimated based on county-level data, to take better countermeasures against COVID-19. We suggested taking time-varying Susceptible-Infected-Recovered (SIR) models with unreported infection rates (UIR) to estimate factual COVID-19 cases in the United States. Methods: Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Around 3% of the studies modeled the effect of asymptomatic individuals on the growth curve of the epidemic. The time-varying SIR model of Peng et al [68] confirmed a 20% contribution of asymptomatic infections to the total infections. Also, Tomochi and Kono [49] included a compartment I in the basic SIR model and reported asymptomatic infections to account for 15% of the COVID-19 infections.…”
Section: What Are the Essential Disease-related Parameters And Most E...mentioning
confidence: 89%
“…Around 3% of the studies modeled the effect of asymptomatic individuals on the growth curve of the epidemic. The time-varying SIR model of Peng et al [68] confirmed a 20% contribution of asymptomatic infections to the total infections. Also, Tomochi and Kono [49] included a compartment I in the basic SIR model and reported asymptomatic infections to account for 15% of the COVID-19 infections.…”
Section: What Are the Essential Disease-related Parameters And Most E...mentioning
confidence: 89%
“…Number of deaths per cause of death from 2011 to 2017 in Italy. Legend: [1] = Infectious and parasitic diseases, [2] = Tumors, [3] = Psychic disorders, diseases of the nervous system and organs of the senses, [4] = Diseases of the circulatory system, [5] = Diseases of the respiratory system, [6] = Diseases of the digestive system, [7] = Other morbid states, [8] = Poorly defined symptoms, signs, and morbid states, [9] = External causes of trauma and poisoning.…”
Section: Resultsmentioning
confidence: 99%
“…Ordinary least squares (OLS) regressions are among the most adopted model by scientists due to their simplicity and efficacy. Specifically, OLS multiple and simple regressions have often been used to predict the course of COVID-19 cases and deaths, both individually and in conjunction with other epidemiological models such as Susceptible-Infected-Recovered (SIR) [8][9][10]. This literature showed that linear regressions are valuable short-term forecasting tools when the necessary assumptions are satisfied.…”
Section: Introductionmentioning
confidence: 99%
“…However, this parameter is highly uncertain in real-world scenarios: It needs to know the number of infections in population, but large portion of infections are not reported, especially those who are asymptomatic. Researchers, including CDC, have conducted several studies [ 47 , [64] , [65] , [66] ] on the prediction for unreported ratio using epidemiological models, to better reflect the full burden of COVID-19. To adapt the current study to general use, the unreported ratio used to calculate the prevalence rate should be updated according to the latest report from the CDC/the department of health or the latest related studies, which could reflect the current epidemiological scenario more accurately.…”
Section: Discussionmentioning
confidence: 99%